Cell Adhesion Molecules and Protein Synthesis Regulation in Neurons - Kozlova, Irina; Sah, Saroj; Keable, Ryan; Leshchyns’ka, Iryna; Janitz, Michael; Sytnyk, Vladimir (Frontiers in Molecular Neuroscience, 2020)
Cell adhesion molecules (CAMs) mediate interactions of neurons with the extracellular environment by forming adhesive bonds with CAMs on adjacent membranes or via binding to proteins of the extracellular matrix. Binding of CAMs to their extracellular ligands results in the activation of intracellular signaling cascades, leading to changes in neuronal structure and the molecular composition and function of neuronal contacts. Ultimately, many of these changes depend on the synthesis of new proteins. In this review, we summarize the evidence showing that CAMs regulate protein synthesis by modulating the activity of transcription factors, gene expression, protein translation and the structure and distribution of organelles involved in protein synthesis and transport.